2012
DOI: 10.1097/hjh.0b013e32835606ae
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of brachial pulse pressure and sialic acid for risk of cardiovascular events during 40 years of follow-up in 37 843 individuals

Abstract: Sialic acid but not PP was an independent risk factor for CVD. The risk induced by PP is highly affected by MAP. This suggests that both estimated arterial stiffness and inflammation contribute through different pathways to risk of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Sialic acid was shown to be positively associated with TNFα and IL-6 [65] and multiple studies have shown positive associations of total serum sialic acid with CVD, stroke and mortality [65][66][67][68]. A recent study reported that sialic acid was an independent risk marker for CVD during 40 years follow-up among Swedish individuals [69]. Taken together, sialic acid is a marker of systemic inflammation that can be used for risk assessment in subjects with CVD, heart failure and T2DM [65][66][67]69,70].…”
Section: Glycoprotein Assays and Cardiometabolic Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…Sialic acid was shown to be positively associated with TNFα and IL-6 [65] and multiple studies have shown positive associations of total serum sialic acid with CVD, stroke and mortality [65][66][67][68]. A recent study reported that sialic acid was an independent risk marker for CVD during 40 years follow-up among Swedish individuals [69]. Taken together, sialic acid is a marker of systemic inflammation that can be used for risk assessment in subjects with CVD, heart failure and T2DM [65][66][67]69,70].…”
Section: Glycoprotein Assays and Cardiometabolic Disordersmentioning
confidence: 98%
“…A recent study reported that sialic acid was an independent risk marker for CVD during 40 years follow-up among Swedish individuals [69]. Taken together, sialic acid is a marker of systemic inflammation that can be used for risk assessment in subjects with CVD, heart failure and T2DM [65][66][67]69,70].…”
Section: Glycoprotein Assays and Cardiometabolic Disordersmentioning
confidence: 99%
“…Sialic acid has been well described in studies of cardiovascular disease as a marker of systemic inflammation and is a predictor of mortality. 36,37 Abnormal sialyation due to a genetic defect is reported as the cause of DCM in a mouse model, possibly via altered Ca 2+ handling. 38 Our results also support an association between sialyation and advanced DCM.…”
Section: Changes In Metabolites Reflect Pathophysiologic Pathways Drmentioning
confidence: 99%
“…Over the past few years, clinical data confirmed the association between circulating SA levels and MS [10,11]. Serum SA levels are often elevated in subjects with MS and serum SA is also a potential risk factor for cardiovascular disease [12]. …”
Section: Introductionmentioning
confidence: 99%